Applied investigation of person-specific and context-specific factors on postoperative recovery and clinical outcomes of patients undergoing gastrointestinal cancer surgery: multicentre European study. Issue 10 (24th October 2016) - Markar, Sheraz R; Mavroveli, Stella; Petrides, Konstantinos V; Scarpa, Marco; Christophe, Veronique; Castoro, Carlo; Mariette, Christophe; Lagergren, Pernilla; Hanna, George B
Abstract : Introduction: Cancer treatments have greatly advanced over the past two decades causing survival improvements and reduced complications from cancer surgery. However, the cancer diagnosis and the effects of treatment modalities pose a major risk to patients' psychological well-being. Given current interest and emerging evidence about the importance of psychological and social factors on cancer survival and coping with cancer treatments, this study will build and expand research in order to identify key modifiable psychosocial variables that contribute to better physical and mental health following gastrointestinal cancer (GIC) surgery. Objectives: To elucidate the incidence of postoperative psychiatric morbidity within 6 months following GIC surgery. To identify key measurable modifiable preoperative psychological factors that can significantly affect postoperative psychiatric morbidity in patients undergoing surgery for GIC. To clarify the changes seen in a patient's psychological well-being during their treatment pathway for GIC. Methods and analysis: This multicentre study has an observational longitudinal study design. In total, 1000 patients will be screened with a multicomponent psychological questionnaire at four different time points: at diagnosis, preoperatively, 1 and 6 months after surgery. Data from this questionnaire will be linked to postoperative complications including psychiatric morbidity, length of hospital stay and recovery to normal activity. Ethics and dissemination: NHS Health Research Authority approval was gained on (REC reference 15.LO/1847) for the completion of this study. Multiple platforms will be used for the dissemination of the research data, including international clinical and patient group presentations and publication of research outputs in a high impact clinical journal.